Получение ультрадисперсных алюмооксидных порошков, модифицированных добавками нанодисперсного диоксида циркония - Саенко, С. Ю. (НТУ "ХПИ", 2015)
В статье представлены результаты исследований по разработке способа получения бимодальных порошковых композиций составов Al₂O₃ – ZrО₂₃ (5 % Y₂O₃) и Al₂O₃ – ZrО₂ (4 % MgO), который основан на насыщении глинозема (γ-Al₂O₃) водными растворами азотнокислых солей Zr, Y и Mg с последующей термообработкой. Данный способ позволяет получить равномерно распределенные в глиноземе нанокристаллические зерна диоксида циркония преимущественно тетрагональной модификации с размером частиц (0,05 – 0,1) мкм, что благоприятно влияет на качественное уплотнение и спекание изделий требуемой формы.

In article the results of researches on development of a method of production bimodal powder compositions of Al₂O₃ – ZrО₂ (5 % Y₂O₃) and Al₂O₃ – ZrО₂ (4 % MgO) are presented, which is based on oxide alumina (γ-Al₂O₃) saturation by water solutions of nitrate Zr, Y and Mg salts with the subsequent heat treatment. It is set that this method allows to produce the nanocrystal grains of dioxide zirconia which are evenly distributed in oxide alumina structure of mainly tetragonal modification with a size of particles 0,05 – 0,1 µm, that favorably influences high-quality consolidation and sintering of products of the demanded form. This method provides the high degree of transformation of transitional forms of alumina oxide into stable modification – corundum (α-Al₂O₃) with fine-grained structure (< 4 µm). Uniform distribution of the modifying additives composition of ZrО₂ – 5 % Y₂O₃ and ZrО₂ – 4 % MgO also promotes the effective growing of material to the high degree of dispersion, that must favourably influence on a quality of samples formation and sintering. The made powders are perspective for production of high density ceramics of different setting.
Production of ultra dispersed alumina powders, modified by additives of nanosized zirconia
Keywords: измельчение; распределение частиц; структура микрокристаллическая; керамика; milling; particle size distribution; phase composition; alumina ceramics